Exclusion of exclusive breastfeeding in children under six months with allergy to cow's milk protein - Barrantes Rojas, Marilyn (2018)
The allergy to cow's milk protein is currently considered an epidemic within the category of non-communicable diseases, is the main cause of allergy in children under one year and continues to increase its incidence around the world, many of the children diagnosed are deprived of exclusive breastfeeding despite the fact that it remains protective against symptoms, which is why it is vitally important that health professionals have the most up-to- date and available information to continue protecting and promoting breastfeeding in these children in a way that strengthens their immune system and monitors the evolution of the infant without jeopardizing the continuity of breastfeeding and its adequate growth and development. The objective of this brief review is to analyze the available scientific evidence regarding the suppression of exclusive breastfeeding in children under 6 months of age with suspected cow's milk protein allergy as a strategy to improve symptoms. The clinical practice based on evidence was used as a methodology, initially a clinical question of prognostic type was raised and the objectives according to this were raised, based on which a set of descriptors was identified from which it was made the search for scientific evidence in different scientific databases.